REDUCTION OF FORMALDEHYDE LEVELS IN TOFU USING WHITE TURMERIC (Curcuma mango) WITH SPECTROPHOTOMETRY - Yazid, Edy Agustian; Putri, Evariza Vyanto (Journal of Islamic Pharmacy, 2017)
Tofu is a type of traditional food that is widely consumed by the community. Tofu is susceptible to damage so manufacturers know often add preservatives such as formaldehyde. Formaldehyde or known as formalin is not included in the list of food additives as they are toxic and harmful to human health. This study aims to determine the decrease in formalin content in tofu using the addition of white turmeric. The method used by spectrophotometry with chromatropic acid as reagent and absorbance is measured at a wavelength of 570 nm. Based on the research results obtained formalin level on tofu before added white turmeric equal to 10.279 ppm. After addition of white turmeric solution with concentration 2.5%; 5% and 7.5%, respectively with soaking for 5 minutes, 10 minutes and 15 minutes obtained the largest decrease of formalin at 7.5% concentration for 15 minutes at 62.8%. From these results it can be concluded that with the addition of white turmeric can reduce formalin in tofu.Â Keywords : Tofu, Formaldehyde, White Turmeric, SpectrophotometryÂ